Forest policy and tribal development : a study of Maharashtra - Ghate, Rucha S. (New Delhi : Concept Pub. Co., 1992)
Economic impact of forest policy on tribals in Mahrashtra.
Includes bibliographical references and index.
Keywords: Forest policy -- India -- Maharashtra; Forest policy -- Economic aspects -- India -- Maharashtra; Tribes -- Economic conditions.# -- India -- Maharashtra